Robust surface coating materials for chemical warfare agent simulant detoxification using ladder-like poly(silsesquioxane) and metal–organic framework composites - Lee, Seungjae; Hur, Seungjae; Jeong, Keunhong; Hwang, Hoesun; Choi, Jungkyu; Khaorapapong, Nithima; Baek, Kyung-Youl; Seo, Jin Young; Yamauchi, Yusuke; Na, Jongbeom (Royal Society of Chemistry, 2024)
As industry experiences rapid growth, toxic chemicals pose a significant threat to humanity and the environment. Among these hazardous substances, chemical warfare agents (CWAs), recognized as some of the most toxic chemicals, have been identified as a top priority for treatment. However, current protective materials for CWAs still rely predominantly on simple physical protection methods such as adsorption and semi-permeable coatings. In this study, we develop mechanically robust composites that can instantly degrade CWAs to less toxic products by incorporating UiO-66 catalysts and branched poly(ethyleneimine) (BPEI) into the polymer matrix. The immobilization of BPEI into a ladder-like poly(silsesquioxane) (LPSQ) matrix leads to superior mechanical properties and processability. Furthermore, the catalytic activity of the UiO-66 catalyst and the BPEI-integrated composite film is systematically evaluated in both non-buffered solutions and gas phases. The resulting novel composite exhibits superior catalytic activity for CWA degradation. This advancement positions composites as promising candidates for application in protective coating materials in the near future.